Socialization of Diarrhea Prevention in School-Age Children Using Healthy Pocket Media at Elementary School UPT 101800 Deli Tua Timur, Deli Tua District, Deli Serdang Regency - Napitupulu, Farida; Sinurat, Sofia Januarti; Tamariahna, Ezra; Simanjuntak, Veronica; Sipayung, Yunita Angelika (Jurnal Kesmas Prima Indonesia, 2026)
Diarrhea remains a major health problem in Indonesia, especially among school-aged children, generally caused by a lack of understanding of personal hygiene and healthy eating habits. This activity aims to increase elementary school students' knowledge about diarrhea prevention through the interactive educational media "Saku Sehat". The socialization was conducted on July 19, 2025, at SD UPT 101800 Delitua Timur, Deli Serdang Regency, involving 37 fifth-grade students. The method used was education and interactive games with the "Saku Sehat" media containing health information, questions and answers, and images of healthy foods. Evaluation was carried out through pre-tests and post-tests, and analyzed using the Wilcoxon Signed-Rank test. The results showed an increase in the average score from 70.00 to 80.27, with a Z value of -3.785 and p = 0.0001, which means the increase was significant. Thus, the "Saku Sehat" media is effective in increasing students' knowledge about diarrhea prevention through a fun and interactive approach.